'I Depend More on Photographs to Help Me Along': The Ngāi Tahu Portraits in Lore and History of the South Island Maori. Issue 3 (3rd July 2018) - Brown, Helen
Abstract : When Lore and History of the South Island Maori was published in 1952 it filled a vacuum in terms of accessible Ngāi Tahu history in the public domain. Despite its scholarly shortcomings, it remained one of the only readily available texts on Ngāi Tahu history for another thirty years. A major element of the publication was its inclusion of photographs, all taken by the author, William Anderson Taylor. Using the Ngāi Tahu portraits in Lore and History as a starting point, and informed where possible by oral interviews with their descendants, this article introduces some of the tribal members who were Taylor's informants, friends, and photographic subjects. Through a reading of the photographs, the article will briefly trace the trajectory of Taylor's relationship with Ngāi Tahu and consider how the visual stories illuminate the text of Lore and History and Taylor's wider body of work with the iwi (tribe) in the first half of the twentieth century. While Taylor is best known as an amateur historian and ethnographer, his photographic practice was also fundamental to his ethnographic research. The photographic contracts that Taylor entered into with the Ngāi Tahu subjects of his photographs created an environment that facilitated exchange, rapport, empathy, and, frequently, enduring bonds.